LINC01541 overexpression attenuates the 17β-Estradiol-induced migration and invasion capabilities of endometrial stromal cells. (4th May 2019) - Mai, Hong; Wei, Yeping; Yin, Yan; Huang, Shijin; Lin, Huisi; Liao, Yan; Liu, Xupeng; Chen, Xianfeng; Shi, Haijuan; Liu, Chuanzhong; Xu, Hong
ABSTRACT: Endometriosis affects 6–10% of healthy women of reproductive age. Therefore, it is important to study the molecular mechanism by which endometriosis develops. This study examined whether aberrant expression of LINC01541 contributes to the pathogenesis of endometriosis. Human endometrial stromal cells (ESCs) were stimulated with 10 nmol/L of 17β-Estradiol (17β-E2) to simulate ectopic cells found in endometriosis. Next, the levels of proteins related to the epithelial-mesenchymal transition (EMT), cell invasion, and metastasis were investigated. The effects of LINCO1541 silencing and overexpression were also examined in ESCs. Cell proliferation and apoptosis were detected by cell counting kit-8 and flow cytometry assays, respectively. ESCs stimulated with 17β-E2 displayed increased levels of N-Cadherin and vimentin expression, but decreased levels of E-Cadherin expression. 17β-E2 promoted the migration and invasion of ESCs, and those affects were partially reversed by overexpression of LINC01541. Furthermore, silencing of LINC01541 attenuated apoptosis and promoted the EMT of ESCs, while overexpression of LINC01541 stimulated cell apoptosis, increased the levels of caspase 3 protein, and decreased the levels of B cell leukemia/lymphoma 2 protein. Overexpression of LINC01541 also decreased the expression of vascular endothelial growth factor A (VEGFA) by repressing the Wnt/β-catenin pathway. Our, results suggest that LINC01541 can inhibit the EMT process, metastasis of ESCs, and VEGFA expression by regulating the Wnt/β-catenin pathway, which may play an important role in the pathogenesis of endometriosis. Abbreviations: ESCs: endometrial stromal cells; 17β-E2: 17β-Estradiol; EMT: epithelial-mesenchymal transition; CASP3: caspase 3; BCL2: B cell leukemia/lymphoma 2; VEGFA: vascular endothelial growth factor A; lncRNA: long non-coding RNA; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; RT-qPCR: reverse transcription-quantitative polymerase chain reaction